THU0681 Establishing the bath ankylosing spondylitis metrology index (BASMI) normative values in a malaysian population: the importance of sex and age factors. (12th June 2018) - Nurul Aain, A.F.; Lau, I.S.; Gun, S.C.; Wahinuddin, S.; Ong, P.S.; Heselynn, H.; Tan, B.E.; Chong, H.C.; Hilmi, A.; Asmah, M.; Asmahan, M.I.; Loh, Y.L.; et al.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic spinal inflammatory disorder which leads to progressive fusion and deformity. The loss of spinal mobility is recognised as an important clinical sign. The BASMI, a composite index of spinal mobility is used internationally in clinical practice and research. However, the interpretation of BASMI has been impeded by the absence of normative values. Objectives: We aimed to attain the normative values for BASMI in Malaysian healthy individuals. Methods: BASMI data of 142 healthy individuals and 187 AS patients were analysed. Each BASMI component was assessed, using the 10-point scoring system, where zero is no mobility and 10 is very severe limitation. Measurements were performed by the rheumatologists and trained researchers following a designated protocol. Data were summarised and analysed according to sex and age groups. Results: The total BASMI scores ranged from 0.2 to 4.2 and 0.6 to 9.6 in the healthy individuals and the AS cases, respectively. There was no significant difference for the BASMI median score between healthy men and women (men=1.2, women=1.6, p>0.05). The estimated median score for healthy individuals aged 15–19 years was 1.2, increasing with age to 2.7 for healthy individuals aged ≥60 years. In AS cases, the estimated median score was 5.4 and 5.8 for men and women, respectively (p>0.05). We observed significant increase of estimated median score between AS patients aged 15–19 years (BASMI score=2.0) and AS patients aged ≥60 years (BASMI score=6.4) (p<0.05). Conclusions: Our data suggest that it is uncommon for healthy individuals to score zero on the BASMI. The magnitude of increase in BASMI score is apparent with increasing age, but not sex in the healthy individuals. Establishment of normative values may aid baseline measurement and monitor change of spinal mobility in AS patients over time, as well as help assess the impact of clinical interventions. Disclosure of Interest: None declared